ANALYSIS THE EFFECT OF LOAN LOSS PROVISION ON BANK PROFITABILITY - Pelealu, Irsa Weinechita; Worang, Frederik G. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: The credit risk is one of the biggest risks facing the banks, and arises from the possibility that loans or bonds held by banks will not be pay back either in part or in full. Therefore, bank should create loan loss provision. The purpose of this research is to examine the impact of loan loss provision on bank profitability. This research is using multiple regression analysis to analyze the effect of independent variables to dependent variable. This research provides the evidence that loan loss provision has not significant positive effect on bank profitability. It means the banking will get profits on loan loss provision but there is possibility to getting losses. The result of this research is also finding the effect of deposits and size of bank has not significant effect on bank profitability, while liabilities have a significant effect on bank profitability. The banking should pay attention to establishment the loan loss provision to anticipate the decline of profitability that will be obtained by the bank itself, or bank should pay attention to whose they have to give credit, so that the credit risk could be anticipated.Keywords: loan loss provision, bank profitability